Developmental language disorders - Nation, K (2008)
Difficulty with language is one of the most common reasons for referral to health professionals during the preschool years. Language difficulties are associated with many developmental disorders, such as autism, but for children with specific language impairment (SLI) language problems are relatively specific. SLI is a neurodevelopmental disorder with heritable bases. Patterns of inheritance are complex, suggesting multiple genes operating probabilistically alongside multiple environmental risk factors. This complexity is mirrored by a complex and heterogeneous phenotype. Children with persistent language impairment are at risk of psychosocial and behaviour problems as well as poor literacy and low educational achievement. A challenge for future work is to understand how genetic and environmental factors impinge on brain development, as well as to develop and refine methods of assessment and intervention. © 2008 Elsevier Ltd. All rights reserved.